2022
DOI: 10.1186/s12888-022-03968-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of suicidal ideation among college students during the COVID-19 pandemic in China: a 3-wave repeated survey

Abstract: Objective The coronavirus disease 2019 (COVID-19) pandemic, a major public health crisis, harms individuals’ mental health. This 3-wave repeated survey aimed to examine the prevalence and correlates of suicidal ideation at different stages of the COVID-19 pandemic in a large sample of college students in China. Methods Using a repeated cross-sectional survey design, we conducted 3 online surveys of college students during the COVID-19 pandemic at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
1
18
1
Order By: Relevance
“…On the other hand, medical students' SI scores and prevalence rates were higher during the pandemic than before. A significant increase in the prevalence of SI among the university student population was commonly reported during the pandemic [49][50][51].The COVID-19 pandemic had a lasting negative impact, with a range of problems brought about by the epidemic, such as restricted activities, limited social and interpersonal interactions, changes in study styles, and possible financial family economic stress. University students' lack of experience in coping with sudden and serious public health events (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, medical students' SI scores and prevalence rates were higher during the pandemic than before. A significant increase in the prevalence of SI among the university student population was commonly reported during the pandemic [49][50][51].The COVID-19 pandemic had a lasting negative impact, with a range of problems brought about by the epidemic, such as restricted activities, limited social and interpersonal interactions, changes in study styles, and possible financial family economic stress. University students' lack of experience in coping with sudden and serious public health events (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, our study lacked measures of variables related to the COVID-19 pandemic, such as experience fighting the outbreak in a high-risk area, working closely with patients with COVID-19, infection of one or more family members or colleagues with COVID-19, the experience of quarantine in a hotel or at home, personal perceptions of or attitudes toward COVID-19, reduced social activities, overwork due to staffing shortages, and lack of medical necessities. Studies have shown that these variables may be associated with suicide ideation and attempts (Farooq et al, 2021 ; Hong et al, 2021 ; Liang et al, 2022 ). Future studies should consider these covariates when examining the association between workplace factors, such as workplace bullying, and nurse suicide to estimate their relationship more accurately.…”
Section: Limitationsmentioning
confidence: 99%
“…The causes of suicide in various countries, cultures, climates, ethnicities, and additional time conditions, especially in crises, due to differences in management control policies, can be different 21,22 . According to the WHO, only 38 countries have a national strategy for suicide prevention.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] The causes of suicide in various countries, cultures, climates, ethnicities, and additional time conditions, especially in crises, due to differences in management control policies, can be different. 21,22 According to the WHO, only 38 countries have a national strategy for suicide prevention. The death rate for suicide reflects the 3.4 goals of the Sustainable Development Goals via 2030 to decrease premature deaths from noncommunicable diseases by one-third.…”
Section: Introductionmentioning
confidence: 99%